Мистическое как рецептивный парадокс: ключевые аспекты поэтики - Chervinska, Olha (Verbum Praha, 2022)
This article, without addressing the question in the aspects of religious, nor ontological, nor as a problem of anthropology nor psychology, is focused on Ƭnding ways to reŹect mystical meanings in a literary text. It emphasizes the intentional dis- sociation of our discourse from the huge artistic experience of the numerous writers who were under the ideological inŹuence of “theory and practice” of the mysterious pilgrim Christian Rosenkreutz and his various followers. The mystical is considered here as “a subject” of analysis of the so-called secular literature. We are facing the prob- lem of receptive reaction to “the beyond”, which can be found out of words, because “the mystical” is transposed into another’s consciousness. For Russian literature on the nineteenth century “the mystical perspective” was not random. Even before the innova- tions of F. Dostoevsky in this regard there were single examples, which, in addition to A. Pushkin, can be found almost everywhere, starting with V. Zhukovsky, M. Lermontov and up to V. Odoyevsky, N. Gogol. The paradox of the mystical’s presence is usually marked by absence of words, by interruption of thought at the peak of existence, graph- ically expressed by aposiopesis (punctuation ellipsis), when the stop of writing actually turns out to be its owing into the mystical dimension (emanation). This article also considers other ways of realization of mystical meanings in a literary text. The receptive paradox is that the mystical is perceived as the real
The Mystical as a Receptive Paradox: Key Aspects of Poetics
Keywords: poetics of the mystical; literary text; emanation of meanings; receptive paradox; classic Russian literature